Program Senam Anti Hipertensi sebagai Upaya Preventif pada Lansia di UPTD Pelayanan Sosial Lanjut Usia Binjai Tahun 2023 - Adelina Sembiring; Lisbet Gurning; Rosmega Rosmega; Beltiana Beltiana; Erika Adelia Turnip (Lembaga Pengembangan Kinerja Dosen, 2024)
Introduction: Hypertension (HTN), defined as systolic blood pressure (SBP) >140 mmHg or diastolic blood pressure (DBP) >90 mmHg, is a major health problem that is growing worldwide. It is the most common risk factor for cardiovascular disease and affects nearly two-thirds of adults aged 60 years or older. The side effects caused by experiencing prolonged high blood pressure are kidney damage (kidney failure), heart (coronary heart disease) and brain which can lead to stroke if not detected early and receive adequate treatment. And can also cause death. Risk factors for complications of hypertension include elderly age, medication compliance, and lifestyle. Empowerment of the elderly can be through non-pharmacological therapy. An example of non-pharmacological therapy is by doing anti-hypertension exercises. The purpose of this program is for the elderly to be able to learn about hypertension and apply how to do anti-hypertension exercises. The method used is providing education to the elderly and applying anti-hypertension exercises with participants (elderly). Implementation of health education and anti-hypertension exercise activities for the elderly at the UPTD for Elderly Social Services in Binjai in November 2023. Most participants were able to answer questions during the question and answer session after the presentation of the material and participants were able to follow the instructor's exercise movement directions. Health education about hypertension and anti-hypertension exercise for the elderly is a program that can help increase physical activity in the elderly which can lower blood pressure in the elderly.